PENGARUH KOMPENSASI, MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DINAS PENDIDIKAN PROVINSI DKI JAKARTA - S, Izlan Sentryo (Gema Pendidikan, 2013)
This research aims to discover the impacts of compensation, motivation, and theorganization’s commitment on the performance of the employees of the Education Agency the Province of Jakarta Special Capital Region. The population of this research are 285 employees of the Education Agency the Province of Jakarta Special Capital Region in 2010. The population reached totals 110 people, namely the employees that belong to category III, college graduates,and have minimal service period of 5 years. Samples of the research are 70 people or 64 percent of the population reached. Sampling is conductedby means of simple random sampling technique. The research method employed is survey; the research instrument is questionnaire, and data analysis is performed by means of descriptive analysis and inferential analysis. The descriptive analysis is employed to describe the state of data on each variable in the form of average, median, modus, standard deviation, variance, frequency distribution, and histograms. Whereas the inferential analysis is employed to test the hypothesis through path analysis.Based on the results of the hypothesis testing through Path Analysis, thisresearch discovers that: (1) Compensation has a direct positive impact on performance, (2) Compensation has a direct positive impact on the organization’s commitment, (3) Motivation has a direct positive impact on performance, (4) Motivation has a direct positive impact on the organization’s commitment; and (5) the organization’s commitment has a direct positive impact on performance.